Le sentiment d’insécurité du « dealer de cité » - Thomas Sauvadet (Sociétés et Jeunesses en Difficulté)
The feelings of insecurity of drug dealers              This article presents three ethnographical studies (two in the Paris suburbs and one in Marseille). It defines and delimits a type of group called “city youths”. Subsequently, the author measures the feeling of insecurity felt by some young people engaged in drug trafficking (principally cocaine and cannabis). This is the most profitable activity and that which gives structure to the type of group studied, particularly as a way of organising the distribution of work and of managing the debt market. The article proposes to explain the complexity of the dealer’s work and attempts to deconstruct the idea that it is « easy money ». At a time when public opinion attaches great importance to feelings of insecurity of “ordinary people” and unthinkingly condemns the “savage youth”, this study attempts to give an understanding of the motives and work of a confirmed dealer (or “city wholesaler”). The author tries to show what leads him to engage in a delinquent or criminal career and to go into a highly competitive world where risks are omnipresent and legal protection does not exist.